2022
DOI: 10.3390/ijerph19095267
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 Vaccination and Vaccine Inequity Worldwide: An Empirical Study Based on Global Data

Abstract: Vaccination is critical for controlling the COVID-19 pandemic. However, the progress of COVID-19 vaccination varies from different countries, and global vaccine inequity has been a worldwide public health issue. This study collected data from the Our World in Data COVID-19 vaccination data set between 13 December 2020 and 1 January 2022. The measurement reflecting the pandemic situation included New cases, New deaths, Hospital patients, ICU patients, and the Reproduction rate. Indicators for measuring the vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 27 publications
0
18
0
1
Order By: Relevance
“…We found that COVID-19 vaccination coverage increased as the HDI increased, suggesting the presence of inequalities in access to vaccines, despite being administered free of charge. Even though this correlation may be affected by the effect of multiple confounders that have not been considered, several studies have described the presence of inequalities in vaccination [ [6] , [7] , [8] ], thus, in-depth analysis of this topic is urgently needed in Peru.…”
Section: Discussionmentioning
confidence: 99%
“…We found that COVID-19 vaccination coverage increased as the HDI increased, suggesting the presence of inequalities in access to vaccines, despite being administered free of charge. Even though this correlation may be affected by the effect of multiple confounders that have not been considered, several studies have described the presence of inequalities in vaccination [ [6] , [7] , [8] ], thus, in-depth analysis of this topic is urgently needed in Peru.…”
Section: Discussionmentioning
confidence: 99%
“…In the midst of the ongoing COVID-19 pandemic, much focus has been placed on access to vaccines, specifically for this virus, highlighting global inequities in access to healthcare and vaccination [ 1 ]. This problem unfortunately is not novel, having persisted since 1974 and extends beyond COVID-19 vaccines to even the most basic of childhood vaccination services [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the midst of the ongoing COVID-19 pandemic, much focus has been placed on access to vaccines, specifically for this virus, highlighting global inequities in access to healthcare and vaccination [ 1 ]. This problem unfortunately is not novel, having persisted since 1974 and extends beyond COVID-19 vaccines to even the most basic of childhood vaccination services [ 1 ]. Communities where children do not receive the suite of basic vaccinations are known as zero-dose communities and are often operationally defined as locations where children have not received the first dose of a Diphtheria, Tetanus and Pertussis vaccine (DTP1), according to GAVI [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…La vacunación es fundamental para controlar la pandemia de la COVID-19, no obstante, su progreso varía según los países, y la inequidad mundial en materia de vacunas ha sido un problema de salud pública mundial. De acuerdo con el índice de desarrollo humano como indicador se identificó que los países de Suramérica tuvieron un moderado nivel de vacunación, además del bajo acceso a vacunación en países de África 12 . Por esta razón, es necesario seguir promoviendo el acceso equitativo al tratamiento, evitando que la disparidad social impacte negativamente en el pronóstico de los pacientes, en búsqueda de mantener el adecuado estado de salud de la población en general, incluidos los pacientes con enfermedades reumatológicas.…”
unclassified